Linguistic Landscape in Arabic Writing Skills Learning: Project-Based Learning Approach - Kiki Cahya Muslimah; Miftahul Huda; R. Taufiqurrochman; Mohammad Affan (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
This research aimed to describe linguistic landscape portrays its project-based learning model to be used a formative test in Arabic writing skills.. The researcher deepens the explanation of the learning stages in a project-based learning approach to create a linguistic landscape project of students' Arabic writing skills. The researcher also analyzed the forms of linguistic landscape projects that are the result of students' Arabic writing skills. The researcher opted to follow Miles and Huberman model which are data collection, data condensation, data display, and conclusion drawing. Therefore, observations, interviews, and documentations are used to collect the data. The conclusion found that Rusydi Ahmad Thu’aimah’s theory brought the level of the writing skills into intermediate level. The linguistic landscape, in a form of a flyer, underwent six synchronic stages of project-based learning. Then the linguistic landscape forms are used not only in the digital version but also in the hand writing version. The teacher offers various language skill models for all students.